2017
DOI: 10.1590/s0102-865020170070000004
|View full text |Cite
|
Sign up to set email alerts
|

Impact of propofol on renal ischemia/reperfusion endoplasmic reticulum stress

Abstract: Purpose: To investigate the protective mechanisms of propofol (Pro) on renal ischemia/reperfusion (I/R) injury by studying its impact on renal I/R endoplasmic reticulum stress. Methods: Eighteen male Sprague-Dawley rats (SD rats) were randomly divided into three groups: the I/R group, the Pro pretreatment group, and the control group, and corresponding treatments were performed. The levels of serum creatinine (Cr) and blood urea nitrogen (BUN) of each group were detected. The expression levels of CCAAT-enhance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…An increase in the number of unfolded proteins leads to ER stress under harmful conditions 9. Studies on the influence of anaesthetic agents on ER stress under specific diseases have been conducted but no study has reported on the association between an anaesthetic agent and ER stress 10,11.…”
Section: Introductionmentioning
confidence: 99%
“…An increase in the number of unfolded proteins leads to ER stress under harmful conditions 9. Studies on the influence of anaesthetic agents on ER stress under specific diseases have been conducted but no study has reported on the association between an anaesthetic agent and ER stress 10,11.…”
Section: Introductionmentioning
confidence: 99%
“…However, lycopene supplementation appeared to be effective in reducing the inflammatory response as represented by the significant decrease in the levels of these two parameters in the lycopene treated group when compared to the control group. Previous studies showed that the serum levels of IL-6 and malondialdehyde (a marker of lipid peroxidation) were significantly increased in response to renal I-R injury in rat model [24]. This is associated with an increases in the mRNA expression of interleukin-6 [25].…”
Section: Discussionmentioning
confidence: 94%
“…In rat models, mitigation of rI/R injury mediated by Pro has been associated with antioxidant and anti-inflammatory effects related to induction of HO-1 expression [33], decreased MDA production [34], reduced expression of immune cellderived mediators of inflammation and oxidative stress such as myeloperoxidase, TNF-α, and IL-1β [35], and prevention of tubular apoptosis [24]. Details on the molecular mechanisms underlying Pro-mediated renoprotection were provided by Wei et al, who showed that Pro preconditioning reduced kidney injury by inhibiting the PI3K/AKT/mTOR axis in a mouse model of rI/R [16], and by Su et al, who reported that Pro preconditioning lessened rI/R injury in rats by preventing endoplasmic reticulum stress [36]. In turn, our preceding research showed that Pro post-conditioning attenuated rI/R-induced acute lung injury by inhibiting autophagy and apoptosis in rat lung cells [11].…”
Section: Agingmentioning
confidence: 99%